Environmental Change Analysis on Agricultural Land Conversion in Palembang City, South Sumatera, Indonesia - Nila Yuliantina; Andy Mulyana; Elisa Wildayana; Andries Lionardo (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The existence of agricultural land is indirectly related to the environment. The existence of agricultural land in terms of environmental aspects can provide five types of benefits, namely preventing flooding, controlling water balance, preventing erosion, and reducing environmental pollution from household waste. This research aims to analyze environmental changes in the conversion of agricultural land to non-agricultural activities in Palembang City. This research uses quantitative methods, analytical quantitative research is conducted to accept or reject hypotheses that are described by significance values. The research also used qualitative methods by conducting measured interviews with 250 respondents. The research was conducted in May 2023 in three sub-districts in Palembang City, namely Kalidoni, Kertapati, and Gandus sub-districts. The environmental indicators used as a reference include water quality, air quality, soil conditions, traffic conditions, runoff water conditions, plant conditions, and animal conditions. The results showed that the condition of plant environmental quality in the Gandus and Kalidoni sub-districts is classified as poor, while the Kertapati sub-district is in the good category. While the condition of the environmental quality of animal indicators in the Kertapati and Kalidoni sub-districts is in the good enough category, but in the Gandus sub-district it is in the bad category. Dragonfly populations will be high if the habitat conditions are very suitable. This means that there are still streams or puddles that are still clean and food is available. This clean water is the place for dragonfly eggs and images for further development. So if the dragonfly population at a location is still high, it means that the water conditions at that location are still not polluted.